High-toughness microalloyed graphene / aluminum composite material and preparation method thereof
By using Sc, Zr, Mg, Si, Cu and Ti elements in aluminum-based composite materials to suppress the interface reaction, and through ball milling and pressure impregnation, the problem of poor compatibility between graphene and aluminum and brittle phases generated by interface reaction is solved, and the preparation of high-toughness microalloyed graphene/aluminum composite materials is achieved.
Patent Information
- Application Number
- CN202411880245.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
As a reinforcement of aluminum-based composite materials, graphene has problems such as poor compatibility and interfacial reaction to produce brittle Al4C3 phase, which affects material performance.
The interfacial reaction between graphene and aluminum is suppressed by Sc, Zr, Mg, Si, Cu and Ti elements. A mixed powder of graphene and microalloy aluminum alloy is prepared by the ball milling and mixing method, and the directional arrangement of graphene and inhibition of interfacial reaction is achieved through pressure impregnation and extrusion deformation technology.
The brittle Al4C3 phase is effectively avoided, the compatibility between graphene and aluminum is improved, the strength and elongation of fracture of the composite material are improved, and the plasticity of the material is significantly enhanced.
Smart Images

Figure CN119640079A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloys, and in particular relates to a high-toughness microalloyed graphene / aluminum composite material and a preparation method thereof. Background Art
[0002] Aluminum and aluminum alloys have the advantages of good plasticity and toughness, high specific strength, good formability, light weight, low density and good corrosion resistance. They have been widely used in many key fields, such as various series of aluminum alloy materials in the aviation and aerospace fields. Due to its low density, it has great application potential in rail transportation and shipbuilding, and is very suitable for use in the engineering field.
[0003] Graphene is a six-membered ring structure composed of sp2 hybridized carbon atoms, with the layers connected by weak van der Waals forces. Due to its unique structure, graphene has excellent mechanical, electrical and thermal conductivity properties and an ultra-large specific surface area. It can be assembled into two-dimensional or three-dimensional materials, and can be used as a reinforcement for aluminum-based composites to enhance the strength and toughness of the material.
[0004] However, under the traditional preparation process, there are significant differences in the morphology, size and quality of graphene nanosheets and aluminum or aluminum alloy powders, resulting in poor compatibility between the two during the material composite process, making it difficult to achieve effective interface bonding. Since graphene is a single atomic layer structure, its surface atomic activity, electronic properties, atomic properties and chemical bonds are different from traditional reinforcement materials. It interacts strongly with alloy elements in the metal matrix, producing brittle Al4C3 phases at the interface, which seriously affects the material performance. Summary of the invention
[0005] In order to solve the problem that graphene has poor compatibility as a reinforcement for aluminum-based composite materials and is prone to produce brittle Al4C3 phase at the interface that affects material properties, the present invention provides a high-toughness microalloyed graphene / aluminum composite material and a preparation method thereof.
[0006] The technical solution of the present invention:
[0007] A method for preparing a high-toughness microalloyed graphene / aluminum composite material, the steps are as follows:
[0008] Step 1: Mix graphene, silicone oil and aluminum alloy powder and perform ball milling to obtain a mixed powder; place the obtained mixed powder under a certain pressure for pressure holding treatment, and then perform heat treatment in a vacuum atmosphere to obtain a preform;
[0009] Step 2: heating and melting pure aluminum, aluminum-scandium alloy and aluminum-zirconium alloy to obtain a mixed liquid, placing the preform obtained in step 1 and the mixed liquid under a certain temperature and pressure for pressure infiltration treatment, and cooling to obtain a sintered composite material;
[0010] Step 3: subjecting the sintered composite material obtained in step 2 to extrusion deformation treatment to obtain an extruded microalloyed graphene / aluminum composite material.
[0011] Furthermore, the method further comprises step 4 of annealing the extruded microalloyed graphene / aluminum composite material obtained in step 3 at 330-350° C. for 0.8-1.2 h to obtain an annealed microalloyed graphene / aluminum composite material.
[0012] Furthermore, the method further comprises step 5, subjecting the annealed microalloyed graphene / aluminum composite material obtained in step 4 to a solution treatment at 530-550° C. for 0.8-1.2 h, water-cooling quenching, and then a aging treatment at 165-185° C. for 5.5-6.5 h to obtain a solution-aged microalloyed graphene / aluminum composite material.
[0013] Furthermore, in step 1, the graphene is a graphene nanosheet produced by a mechanical exfoliation process; the aluminum alloy powder is a 6061 aluminum alloy powder, and the chemical composition of the 6061 aluminum alloy powder includes, by weight percentage: Mg: 0.8-1.2%, Si: 0.4-0.8%, Cu: 0.15-0.4%, Mn: 0.15%, Cr: 0.04-0.35%, Ti: 0.15%, Fe: 0.7%, and the rest is Al and unavoidable impurities; the mass ratio of the graphene, silicone oil and aluminum alloy powder is 0.5-0.8:2-4:95-97.
[0014] Furthermore, the ball milling in step 1 uses zirconia balls as ball milling media, the ball-to-material ratio is 5:1, the ball milling speed is 200-300 r / min, and the ball milling time is 1.5-2.5 h; the ball milling process is carried out in the form of forward rotation for 8-12 min → pause for 18-22 min → flip over for 8-12 min → pause for 18-22 min.
[0015] Furthermore, the pressure of the pressure-maintaining treatment in step 1 is 55-65 MPa for 5-15 minutes, and the temperature of the heat treatment in step 1 is 390-410° C. for 5.5-6.5 hours.
[0016] Furthermore, in step 2, the amount of aluminum-scandium alloy added to the mixed liquid is controlled according to the mass percentage of scandium element in the final product of 0.2-0.3%, and the amount of aluminum-zirconium alloy added to the mixed solution is controlled according to the mass percentage of zirconium element in the final product of 0.4-0.5%; the mass ratio of the preform to the mixed liquid is 6:4.
[0017] Furthermore, the temperature of the pressure penetration treatment in step 2 is 840-860° C., the pressure is 9.5-10.5 MPa, and the pressure holding time is 6-10 min.
[0018] Furthermore, the temperature of the extrusion treatment in step 3 is 440-460° C., the extrusion ratio is 10:1, and the extrusion speed is 0.2-0.4 mm / min.
[0019] The invention discloses a method for preparing a high-toughness microalloyed graphene / aluminum composite material. The prepared high-toughness microalloyed graphene / aluminum composite material contains the following alloy components in percentage by weight: Mg: 1.4-1.5%, Si: 0.9-1.0%, Cu: 0.2-0.3%, Cr: 0.08-0.1%, Fe: 0.1-0.3%, Zr: 0.4-0.5%, Sc: 0.1-0.3%, and the rest are Al and other inevitable impurity elements.
[0020] Beneficial effects of the present invention:
[0021] The preparation method of the microalloyed graphene / aluminum composite material provided by the present invention inhibits the interface reaction between graphene and aluminum by using Sc, Zr, Mg, Si, Cu and Ti elements, thereby avoiding the generation of brittle Al4C3 phase; graphene and microalloyed aluminum alloy mixed powder are prepared by a ball milling powder mixing method, trace alloying elements are added to the graphene / aluminum composite material by using a pressure infiltration technology, and the graphene is directional arranged by extrusion deformation. After extrusion deformation, the grains are preferentially oriented, and the grains tend to be elongated along the extrusion direction, thereby solving the problem of poor compatibility of graphene / aluminum in the material composite process and overcoming the difficulty of achieving effective interface bonding between graphene and aluminum.
[0022] Through the preparation method of the present invention, graphene is evenly dispersed in the aluminum-based composite material, and no obvious agglomeration phenomenon is found. Compared with the existing graphene / aluminum composite material, the microalloyed graphene / aluminum composite material prepared by the present invention has an elongation at break from 5% to 7.5% while maintaining a strength of more than 300MPa, an increase of nearly 50%, and the plasticity of the composite material is significantly improved. There are more and more fine dimples on the fracture surface, all showing the characteristics of ductile fracture, which confirms the effect of microalloying. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The actual photographs of the sintered composite material sample and the extruded composite material sample prepared in Example 1, a is the sintered composite material, b is the extruded composite material;
[0024] Figure 2 These are metallographic photographs of the solution-aged microalloyed graphene / aluminum composite material prepared in Example 1, wherein a is a metallographic photograph magnified 50 times, b is a metallographic photograph magnified 100 times, c is a metallographic photograph magnified 200 times, and d is a metallographic photograph magnified 500 times;
[0025] Figure 3 The SEM microstructure photos and element distribution characterization pictures of the solution-aged microalloyed graphene / aluminum composite material prepared in Example 1, a is a low-magnification SEM photo, b is a distribution characterization picture of the Al element, c is a distribution characterization picture of the Si element, d is a distribution characterization picture of the C element, and e and f are SEM pictures after different magnifications;
[0026] Figure 4 This is a high-resolution transmission photograph of the interface of the solution-aged microalloyed graphene / aluminum composite material prepared in Example 1;
[0027] Figure 5 Element distribution characterization diagram of the interface of the solution-aged microalloyed graphene / aluminum composite material prepared in Example 1, a is a dark field phase characterization diagram of the interface, b is an Al element distribution characterization diagram, c is a C element distribution characterization diagram, d is a Mg element distribution characterization diagram, e is a Si element distribution characterization diagram, and f is a Cu element distribution characterization diagram;
[0028] Figure 6 This is a microscopic picture of the interface structure of the solution-aged microalloyed graphene / aluminum composite material prepared in Example 1.
[0029] Figure 7 It is a comparison diagram of the tensile strength and tensile strain rate of pure aluminum and graphene / pure aluminum composites, 6061 aluminum alloy and graphene / 6061 aluminum alloy composites, a is pure aluminum and graphene / pure aluminum composites, b is 6061 aluminum alloy and graphene / 6061 aluminum alloy composites, the horizontal axis is the tensile strain rate, and the vertical axis is the tensile strength;
[0030] Figure 8 A comparison chart of tensile strength and tensile strain rate of the annealed composite material sample and the solution-aged composite material sample prepared in Example 1;
[0031] Fig. 9 The tensile fracture scanning photos of the annealed composite material sample prepared in Example 1, a is magnified 100 times, b is magnified 200 times, c is magnified 500 times, and d is magnified 1000 times;
[0032] Fig.10 These are scanning photos of the tensile fracture of the solution-aged composite material sample prepared in Example 1, where a is magnified 1000 times, b is magnified 2000 times, c is magnified 5000 times, and d is magnified 10000 times. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0034] Example 1
[0035] This embodiment provides a high-toughness microalloyed graphene / aluminum composite material and a preparation method thereof.
[0036] The steps of the preparation method of the high-toughness microalloyed graphene / aluminum composite material in this embodiment are as follows:
[0037] Step 1: Preparation of prepolymer:
[0038] In this embodiment, graphene nanosheets composed of sheet-like stacked nanosheets produced by a mechanical exfoliation process are used as reinforcement.
[0039] In this embodiment, the graphene / aluminum interface reaction is suppressed by Sc, Zr, Mg, Si, Cu and Ti elements, because Mg, Si, Cu and Ti elements exist in 6061 aluminum alloy, and high-purity 6061 aluminum alloy has good plasticity and machinability. Therefore, high-purity 6061 aluminum alloy powder is used as the preparation matrix of the preform. The original 6061 aluminum alloy powder is composed of particles of various shapes and generally ellipsoidal. The particle size of the powder is distributed between 2 and 18 μm, and its average particle size is 7 μm. The chemical composition of the 6061 aluminum alloy powder used in this embodiment includes, by weight percentage: Mg: 1.0%, Si: 0.6%, Cu: 0.2%, Mn: 0.15%, Cr: 0.10%, Ti: 0.15%, Fe: 0.7%, and the rest is Al and unavoidable impurities.
[0040] In this embodiment, dimethyl silicone oil is introduced as a process control agent during the graphene dispersion process, and the molecular formula is [Si(CH3)2O] n , assisting the dispersion of graphene and suppressing interfacial reactions.
[0041] In order to evenly disperse the graphene and aluminum alloy powders, this embodiment first uses a planetary ball mill (YXQM-2L) for mechanical ball milling, and uses high temperature resistant and wear resistant zirconia balls as ball milling media, with a ball-to-material ratio of 5:1.
[0042] 0.6g of graphene, 1.8g of dimethyl silicone oil, 57.6g of 6061 aluminum alloy powder and 300g of zirconium oxide balls were added to the ball mill, the ball milling speed was 250r / min, and the ball milling time was 2h. During the ball milling process, in order to avoid the high temperature of the tank body caused by long-term ball milling, the ball milling was carried out in the form of forward rotation for 10min → pause for 20min → flip for 10min → pause for 20min to obtain a mixed powder.
[0043] The mixed powder obtained by ball milling was used to prepare a prepolymer under a 200T experimental press. The mixed powder was placed in a Φ64 steel mold and maintained at a pressure of 60MPa for 10min. Then, it was placed in a vacuum atmosphere furnace (model GWL-1600ZQLB) and heat treated at 400℃ for 6h to obtain a preform.
[0044] Step 2: Preparation of sintered composite material:
[0045] 17.9g of pure aluminum, 10.6g of aluminum-zirconium alloy and 11.5g of aluminum-scandium alloy are heated and melted to obtain a mixed liquid, wherein the mass fraction of scandium in the aluminum-scandium alloy is 0.02%, and the amount of scandium added is controlled according to the mass percentage of scandium element in the final product of 0.2-0.3%, and the mass fraction of zirconium in the aluminum-zirconium alloy is 0.05%, and the amount of zirconium added is controlled according to the mass percentage of zirconium element in the final product of 0.4-0.5%.
[0046] 40g of the mixed liquid and the preform obtained in step 1 are subjected to pressure infiltration treatment at a temperature of 850°C, a pressure of 10MPa, and a holding time of 8min. The preform melts into liquid at a high temperature of 850°C, and is infiltrated and fused with the mixed liquid under pressure, and becomes a sintered composite material after cooling.
[0047] Step 3: Preparation of extruded microalloyed graphene / aluminum composite materials:
[0048] The sintered composite material obtained in step 2 is subjected to extrusion deformation treatment, the extrusion treatment temperature is 450° C., the extrusion ratio is 10:1, and the extrusion speed is 0.3 mm / min to obtain an extruded microalloyed graphene / aluminum composite material.
[0049] Step 4: Preparation of annealed microalloyed graphene / aluminum composite material:
[0050] The extruded microalloyed graphene / aluminum composite material obtained in step 3 was subjected to annealing treatment at 340° C. for 1.0 h to obtain an annealed microalloyed graphene / aluminum composite material.
[0051] Step 5: Preparation of solid solution-aged microalloyed graphene / aluminum composite materials:
[0052] The annealed microalloyed graphene / aluminum composite material obtained in step 4 was subjected to a solution treatment at 540° C. for 1.0 h, water-quenched, and then subjected to an aging treatment at 175° C. for 6.0 h to obtain a solution-aged microalloyed graphene / aluminum composite material.
[0053] The solution-aged samples were tested and the microalloyed graphene / aluminum composite material contained the following alloy components in weight percentage: Mg: 1.44%, Si: 0.95%, Cu: 0.27%, Cr: 0.1%, Fe: 0.14%, Zr: 0.46%, Sc: 0.15%, and the rest were Al and other inevitable impurity elements.
[0054] Example 2
[0055] This embodiment provides a high-toughness microalloyed graphene / aluminum composite material and a preparation method thereof.
[0056] The steps of the preparation method of the high-toughness microalloyed graphene / aluminum composite material in this embodiment are as follows:
[0057] Step 1: Preparation of prepolymer:
[0058] In this embodiment, graphene nanosheets composed of sheet-like stacked nanosheets produced by a mechanical exfoliation process are used as reinforcement.
[0059] In this embodiment, the graphene / aluminum interface reaction is suppressed by Sc, Zr, Mg, Si, Cu and Ti elements, because Mg, Si, Cu and Ti elements exist in 6061 aluminum alloy, and high-purity 6061 aluminum alloy has good plasticity and machinability. Therefore, high-purity 6061 aluminum alloy powder is used as the preparation matrix of the preform. The original 6061 aluminum alloy powder is composed of particles of various shapes and generally ellipsoidal. The particle size of the powder is distributed between 2 and 18 μm, and its average particle size is 7 μm. The chemical composition of the 6061 aluminum alloy powder used in this embodiment includes, by weight percentage: Mg: 0.8%, Si: 0.8%, Cu: 0.3%, Mn: 0.15%, Cr: 0.2%, Ti: 0.15%, Fe: 0.7%, and the rest is Al and unavoidable impurities.
[0060] In this embodiment, dimethyl silicone oil is introduced as a process control agent during the graphene dispersion process, and the molecular formula is [Si(CH3)2O] n , assisting the dispersion of graphene and suppressing interfacial reactions.
[0061] In order to evenly disperse the graphene and aluminum alloy powders, this embodiment first uses a planetary ball mill (YXQM-2L) for mechanical ball milling, and uses high temperature resistant and wear resistant zirconia balls as ball milling media, with a ball-to-material ratio of 5:1.
[0062] 0.6g of graphene, 1.8g of dimethyl silicone oil, 57.6g of 6061 aluminum alloy powder and 300g of zirconium oxide balls were added to the ball mill, the ball milling speed was 200r / min, and the ball milling time was 2.5h. During the ball milling process, in order to avoid the high temperature of the tank body caused by long-term ball milling, the ball milling was carried out in the form of forward rotation for 8min → pause for 18min → flip for 8min → pause for 18min to obtain a mixed powder.
[0063] The mixed powder obtained by ball milling was used to prepare a prepolymer under a 200T experimental press. The mixed powder was placed in a Φ64 steel mold and maintained at a pressure of 55MPa for 15min. It was then placed in a vacuum atmosphere furnace (model GWL-1600ZQLB) and heat treated at 390°C for 6.5h to obtain a preform.
[0064] Step 2: Preparation of sintered composite material:
[0065] 17.9g of pure aluminum, 10.6g of aluminum-zirconium alloy and 11.5g of aluminum-scandium alloy are heated and melted to obtain a mixed liquid, wherein the mass fraction of scandium in the aluminum-scandium alloy is 0.02%, and the amount of scandium added is controlled according to the mass percentage of scandium element in the final product of 0.2-0.3%, and the mass fraction of zirconium in the aluminum-zirconium alloy is 0.05%, and the amount of zirconium added is controlled according to the mass percentage of zirconium element in the final product of 0.4-0.5%.
[0066] 40g of the mixed liquid and the preform obtained in step 1 are subjected to pressure infiltration treatment at a temperature of 840°C, a pressure of 9.5MPa, and a holding time of 10min. The preform melts into liquid at high temperature, and is infiltrated and fused with the mixed liquid under pressure, and becomes a sintered composite material after cooling.
[0067] Step 3: Preparation of extruded microalloyed graphene / aluminum composite materials:
[0068] The sintered composite material obtained in step 2 is subjected to extrusion deformation treatment, the extrusion treatment temperature is 440° C., the extrusion ratio is 10:1, and the extrusion speed is 0.2 mm / min to obtain an extruded microalloyed graphene / aluminum composite material.
[0069] Step 4: Preparation of annealed microalloyed graphene / aluminum composite material:
[0070] The extruded microalloyed graphene / aluminum composite material obtained in step 3 was subjected to annealing treatment at 330° C. for 1.2 h to obtain an annealed microalloyed graphene / aluminum composite material.
[0071] Step 5: Preparation of solid solution-aged microalloyed graphene / aluminum composite materials:
[0072] The annealed microalloyed graphene / aluminum composite material obtained in step 4 was subjected to a solution treatment at 530° C. for 0.8 h, water-cooled quenching, and then subjected to an aging treatment at 165° C. for 6.5 h to obtain a solution-aged microalloyed graphene / aluminum composite material.
[0073] The sample obtained in this embodiment was tested. The microalloyed graphene / aluminum composite material contained the following alloy components in weight percentage: Mg: 1.41%, Si: 0.99%, Cu: 0.25%, Cr: 0.1%, Fe: 0.27%, Zr: 0.44%, Sc: 0.16%, and the rest were Al and other inevitable impurity elements.
[0074] The high-toughness microalloyed graphene / aluminum composite material prepared in this embodiment has a tensile strength of 286 MPa and an elongation after fracture of 12%.
[0075] Example 3
[0076] This embodiment provides a high-toughness microalloyed graphene / aluminum composite material and a preparation method thereof.
[0077] The steps of the preparation method of the high-toughness microalloyed graphene / aluminum composite material in this embodiment are as follows:
[0078] Step 1: Preparation of prepolymer:
[0079] In this embodiment, graphene nanosheets composed of sheet-like stacked nanosheets produced by a mechanical exfoliation process are used as reinforcement.
[0080] In this embodiment, the graphene / aluminum interface reaction is suppressed by Sc, Zr, Mg, Si, Cu and Ti elements, because Mg, Si, Cu and Ti elements exist in 6061 aluminum alloy, and high-purity 6061 aluminum alloy has good plasticity and machinability. Therefore, high-purity 6061 aluminum alloy powder is used as the preparation matrix of the preform. The original 6061 aluminum alloy powder is composed of particles of various shapes and generally ellipsoidal. The particle size of the powder is distributed between 2 and 18 μm, and its average particle size is 7 μm. The chemical composition of the 6061 aluminum alloy powder used in this embodiment includes, by weight percentage: Mg: 1.2%, Si: 0.5%, Cu: 0.4%, Mn: 0.15%, Cr: 0.3%, Ti: 0.15%, Fe: 0.7%, and the rest is Al and unavoidable impurities.
[0081] In this embodiment, dimethyl silicone oil is introduced as a process control agent during the graphene dispersion process, and the molecular formula is [Si(CH3)2O] n , assisting the dispersion of graphene and suppressing interfacial reactions.
[0082] In order to evenly disperse the graphene and aluminum alloy powders, this embodiment first uses a planetary ball mill (YXQM-2L) for mechanical ball milling, and uses high temperature resistant and wear resistant zirconia balls as ball milling media, with a ball-to-material ratio of 5:1.
[0083] 0.6g of graphene, 1.8g of dimethyl silicone oil, 57.6g of 6061 aluminum alloy powder and 300g of zirconium oxide balls were added to the ball mill, the ball milling speed was 300r / min, and the ball milling time was 1.5h. During the ball milling process, in order to avoid the high temperature of the tank body caused by long-term ball milling, the ball milling was carried out in the form of forward rotation for 12min → pause for 22min → flip for 12min → pause for 22min to obtain a mixed powder.
[0084] The mixed powder obtained by ball milling was used to prepare a prepolymer under a 200T experimental press. The mixed powder was placed in a Φ64 steel mold and maintained at a pressure of 65MPa for 5min. It was then placed in a vacuum atmosphere furnace (model GWL-1600ZQLB) and heat treated at 410°C for 5.5h to obtain a preform.
[0085] Step 2: Preparation of sintered composite material:
[0086] 17.9g of pure aluminum, 10.6g of aluminum-zirconium alloy and 11.5g of aluminum-scandium alloy are heated and melted to obtain a mixed liquid, wherein the mass fraction of scandium in the aluminum-scandium alloy is 0.02%, and the amount of scandium added is controlled according to the mass percentage of scandium element in the final product of 0.2-0.3%, and the mass fraction of zirconium in the aluminum-zirconium alloy is 0.05%, and the amount of zirconium added is controlled according to the mass percentage of zirconium element in the final product of 0.4-0.5%.
[0087] 40g of the mixed liquid and the preform obtained in step 1 are subjected to pressure infiltration treatment at a temperature of 860°C, a pressure of 10.5MPa, and a holding time of 6min. The preform melts into liquid at high temperature, and is infiltrated and fused with the mixed liquid under pressure, and becomes a sintered composite material after cooling.
[0088] Step 3: Preparation of extruded microalloyed graphene / aluminum composite materials:
[0089] The sintered composite material obtained in step 2 is subjected to extrusion deformation treatment, the extrusion treatment temperature is 460° C., the extrusion ratio is 10:1, and the extrusion speed is 0.4 mm / min to obtain an extruded microalloyed graphene / aluminum composite material.
[0090] Step 4: Preparation of annealed microalloyed graphene / aluminum composite material:
[0091] The extruded microalloyed graphene / aluminum composite material obtained in step 3 was subjected to annealing treatment at 350° C. for 0.8 h to obtain an annealed microalloyed graphene / aluminum composite material.
[0092] Step 5: Preparation of solid solution-aged microalloyed graphene / aluminum composite materials:
[0093] The annealed microalloyed graphene / aluminum composite material obtained in step 4 was subjected to a solution treatment at 550° C. for 1.2 h, water-cooled quenching, and then subjected to an aging treatment at 185° C. for 5.5 h to obtain a solution-aged microalloyed graphene / aluminum composite material.
[0094] The sample obtained in this embodiment was tested. The microalloyed graphene / aluminum composite material contained the following alloy components in weight percentage: Mg: 1.40%, Si: 0.96%, Cu: 0.24%, Cr: 0.09%, Fe: 0.20%, Zr: 0.48%, Sc: 0.17%, and the rest were Al and other inevitable impurity elements.
[0095] Comparative Example 1
[0096] This comparative example provides a graphene / pure aluminum composite material and a preparation method thereof.
[0097] The preparation method of the graphene / pure aluminum composite material of this comparative example is as follows:
[0098] Step 1: Preparation of prepolymer:
[0099] In this comparative example, graphene nanosheets composed of sheet-like stacked nanosheets produced by a mechanical exfoliation process are used as reinforcement.
[0100] In this comparative example, dimethyl silicone oil was introduced as a process control agent during the graphene dispersion process, and its molecular formula is [Si(CH3)2O] n , assisting the dispersion of graphene and suppressing interfacial reactions.
[0101] In order to evenly disperse the graphene and pure aluminum powder, this embodiment first uses a planetary ball mill (YXQM-2L) for mechanical ball milling, and uses high temperature resistant and wear resistant zirconia balls as ball milling media, with a ball-to-material ratio of 5:1.
[0102] 0.6g of graphene, 1.8g of dimethyl silicone oil, 57.6g of pure aluminum powder and 300g of zirconium oxide balls were added to the ball mill, the ball milling speed was 250r / min, and the ball milling time was 2h. During the ball milling process, in order to avoid the high temperature of the tank body caused by long-term ball milling, the carbon-aluminum reaction was added to generate Al4C3, and the ball milling was carried out in the form of forward rotation for 10min → pause for 20min → flip 10min → pause for 20min to obtain a mixed powder.
[0103] The mixed powder obtained by ball milling was used to prepare a prepolymer under a 200T experimental press. The mixed powder was placed in a Φ64 steel mold and maintained at a pressure of 60MPa for 10min. Then, it was placed in a vacuum atmosphere furnace (model GWL-1600ZQLB) and heat treated at 400℃ for 6h to obtain a preform.
[0104] Step 2: Preparation of sintered composite material:
[0105] 40g of pure aluminum is heated and melted to obtain pure aluminum liquid, and the 40g of pure aluminum liquid and the preform obtained in step 1 are subjected to pressure infiltration treatment, and the temperature of the pressure infiltration treatment is 850°C, the pressure is 10MPa, and the pressure holding time is 8min. The preform is melted into liquid at a high temperature of 850°C, and the preform is infiltrated and fused with the mixed liquid under pressure, and becomes a sintered composite material after cooling.
[0106] Step 3: Preparation of extruded graphene / pure aluminum composite material:
[0107] The sintered composite material obtained in step 2 is subjected to extrusion deformation treatment, the extrusion treatment temperature is 450° C., the extrusion ratio is 10:1, and the extrusion speed is 0.3 mm / min to obtain an extruded graphene / pure aluminum composite material.
[0108] Step 4: Preparation of annealed graphene / pure aluminum composite material:
[0109] The extruded graphene / pure aluminum composite material obtained in step 3 is subjected to annealing treatment at 340° C. for 1.0 h to obtain an annealed graphene / pure aluminum composite material.
[0110] Step 5: Preparation of solid solution aged graphene / pure aluminum composite material:
[0111] The annealed graphene / pure aluminum composite material obtained in step 4 is subjected to a solution treatment at 540° C. for 1.0 h, water-cooled quenching, and then subjected to an aging treatment at 175° C. for 6.0 h to obtain a solution-aged graphene / pure aluminum composite material.
[0112] Comparative Example 2
[0113] This comparative example provides a graphene / 6061 aluminum alloy composite material and a preparation method thereof.
[0114] The preparation method of the graphene / 6061 aluminum alloy composite material of this comparative example is as follows:
[0115] Step 1: Preparation of prepolymer:
[0116] In this embodiment, graphene nanosheets composed of sheet-like stacked nanosheets produced by a mechanical exfoliation process are used as reinforcement.
[0117] The original 6061 aluminum alloy powder is composed of particles of various shapes and generally ellipsoidal shapes, and the particle size of the powder is distributed between 2 and 18 μm, and the average particle size is 7 μm. The chemical composition of the 6061 aluminum alloy powder used in this comparative example includes, by weight percentage, Mg: 1.0%, Si: 0.6%, Cu: 0.2%, Mn: 0.15%, Cr: 0.10%, Ti: 0.15%, Fe: 0.7%, and the rest is Al and unavoidable impurities.
[0118] In this comparative example, dimethyl silicone oil was introduced as a process control agent during the graphene dispersion process, and its molecular formula is [Si(CH3)2O] n , assisting the dispersion of graphene and suppressing interfacial reactions.
[0119] In order to evenly disperse the graphene and aluminum alloy powders, this embodiment first uses a planetary ball mill (YXQM-2L) for mechanical ball milling, and uses high temperature resistant and wear resistant zirconia balls as ball milling media, with a ball-to-material ratio of 5:1.
[0120] 0.6g of graphene, 1.8g of dimethyl silicone oil, 57.6g of 6061 aluminum alloy powder and 300g of zirconium oxide balls were added to the ball mill, the ball milling speed was 250r / min, and the ball milling time was 2h. During the ball milling process, in order to avoid the high temperature of the tank body caused by long-term ball milling, the ball milling was carried out in the form of forward rotation for 10min → pause for 20min → flip for 10min → pause for 20min to obtain a mixed powder.
[0121] The mixed powder obtained by ball milling was used to prepare a prepolymer under a 200T experimental press. The mixed powder was placed in a Φ64 steel mold and maintained at a pressure of 60MPa for 10min. Then, it was placed in a vacuum atmosphere furnace (model GWL-1600ZQLB) and heat treated at 400℃ for 6h to obtain a preform.
[0122] Step 2: Preparation of sintered composite material:
[0123] 40g of 6061 aluminum alloy is heated and melted to obtain aluminum alloy liquid, and 40g of aluminum alloy liquid and the preform obtained in step 1 are subjected to pressure infiltration treatment, and the temperature of the pressure infiltration treatment is 850°C, the pressure is 10MPa, and the holding time is 8min. The preform is melted into liquid at a high temperature of 850°C, and the preform is infiltrated and fused with the mixed liquid under pressure, and becomes a sintered composite material after cooling.
[0124] Step 3: Preparation of extruded graphene / 6061 aluminum alloy composite material:
[0125] The sintered composite material obtained in step 2 was subjected to extrusion deformation treatment, the extrusion treatment temperature was 450° C., the extrusion ratio was 10:1, and the extrusion speed was 0.3 mm / min to obtain an extruded graphene / 6061 aluminum alloy composite material.
[0126] Step 4: Preparation of annealed microalloyed graphene / 6061 aluminum alloy composite material:
[0127] The extruded graphene / 6061 aluminum alloy composite material obtained in step 3 was subjected to annealing treatment at 340° C. for 1.0 h to obtain an annealed microalloyed graphene / 6061 aluminum alloy composite material.
[0128] Step 5: Preparation of solution-aged microalloyed graphene / 6061 aluminum alloy composite material:
[0129] The annealed microalloyed graphene / 6061 aluminum alloy composite material obtained in step 4 was subjected to a solution treatment at 540° C. for 1.0 h, water-quenched, and then subjected to an aging treatment at 175° C. for 6.0 h to obtain a solution-aged microalloyed graphene / 6061 aluminum alloy composite material.
[0130] The high-toughness microalloyed graphene / aluminum composite material prepared in this embodiment has a tensile strength of 280 MPa and an elongation after fracture of 8%.
[0131] 1. Metallographic structure characterization of the solution-aged microalloyed graphene / aluminum composite material prepared in this example
[0132] The sample was cut into 10mm×10mm×5mm specimens, and polished with 120#, 240#, 400#, 600#, 800#, 1000#, and 2000# sandpapers, followed by vibration electrolytic polishing. The electrolyte was 10% perchloric acid + 90% methanol, the current was 0.9A~1.1A, the time was 45s~60s, the temperature was liquid nitrogen cooling -25~30℃, the surface alcohol was blown dry with a blower, and finally observed with a metallographic microscope.
[0133] Figure 2 are metallographic photographs of the solution-aged microalloyed graphene / aluminum composite material prepared in this embodiment, a is a metallographic photograph magnified 50 times, b is a metallographic photograph magnified 100 times, c is a metallographic photograph magnified 200 times, and d is a metallographic photograph magnified 500 times; Figure 2 It can be seen from the metallographic structure that the composite material as a whole is directional due to extrusion, the graphene does not undergo serious agglomeration in the aluminum matrix, the black strip-like areas are broken up, the size becomes smaller, and the dispersion becomes more uniform.
[0134] 2. Scanning electron microscope (SEM) microstructure characterization of the solid solution-aged microalloyed graphene / aluminum composite material prepared in this example
[0135] Scanning electron microscope is an important device for material structure characterization. Compared with metallographic microscope, scanning electron microscope has a larger magnification and higher resolution, and can obtain clearer microstructure photos.
[0136] Figure 3 The SEM microstructure photos and element distribution characterization pictures of the solution-aged microalloyed graphene / aluminum composite material prepared in this embodiment, a is a low-magnification SEM photo, b is a distribution characterization picture of the Al element, c is a distribution characterization picture of the Si element, d is a distribution characterization picture of the C element, and e and f are SEM pictures after different magnifications; Figure 3 It can be seen that the solution-aged microalloyed graphene / aluminum composite material has a high density, no obvious defects, and the process inhibitor is evenly dispersed without obvious aggregation. In the low-magnification SEM image, preliminary evidence of the existence of graphene and the distribution of its surrounding elements can be found, providing a reference for further research on the interface morphology of the composite material.
[0137] 3. Transmission electron microscopy (TEM) microstructure characterization of the solution-aged microalloyed graphene / aluminum composite material prepared in this embodiment
[0138] The in-situ multifunctional transmission electron microscope Tolos F200X was used to observe and analyze the structure of the composite material, mainly observing the structure morphology and graphene geometry, number of layers, interface composition, etc. The samples were observed using high-angle annular dark field-scanning transmission imaging mode (HAADF-STEM). The transmission sample preparation process is as follows: first, the sample line is cut to 0.5mm, then 800#, 1500# and 2000# sandpaper are used to grind and thin the two sides of the sample to 50μm, and then the thin slice is ion thinned using an ion thinning instrument.
[0139] Figure 4 This is a high-resolution transmission photograph of the interface of the solution-aged microalloyed graphene / aluminum composite material prepared in this embodiment; Figure 4 It can be seen that there is a clear color contrast between the aluminum matrix and graphene. The graphene appears in dark black strips, while the matrix is slightly lighter in color. The graphene is oriented in one direction in the composite material after extrusion deformation, and the directions of the four black strips of graphene observed are basically parallel to each other. The matrix alloy is deformed after extrusion, and the grains are oriented in a direction that is basically parallel to the extrusion direction. No interfacial reaction products, namely the needle-shaped brittle phase Al4C3, were found within the field of view, indicating that the added alloying elements have a significant inhibitory effect on the interfacial reaction.
[0140] Figure 5This is an element distribution characterization diagram of the interface of the solution-aged microalloyed graphene / aluminum composite material prepared in this embodiment, a is a dark field phase characterization diagram of the interface, b is an Al element distribution characterization diagram, c is a C element distribution characterization diagram, d is a Mg element distribution characterization diagram, e is a Si element distribution characterization diagram, and f is a Cu element distribution characterization diagram; the transmission imaging mode under the HAADF mode can utilize the large difference in atomic number between C atoms and Al atoms to form a light and dark contrast. As can be seen from a, there are black strip-shaped areas under the light and dark contrast. Combined with the distribution of carbon elements, it can be determined that the strip-shaped area surrounded by the yellow dotted line in Figure a is graphene; as can be seen from Figure d, the Mg element is mainly distributed at the neighboring interface of graphene / aluminum, and there are a large number of Mg elements around the strip-shaped graphene area; no needle-shaped phase interface reaction product Al4C3 was found at the interface between graphene and aluminum matrix, indicating that the graphene / aluminum interface reaction was suppressed; Figure d shows the distribution of the Cu element. It can be observed that the Cu element is widely and evenly distributed over a large area. Compared with several other elements, the Cu element is more evenly distributed.
[0141] Figure 6 This is a microscopic picture of the interface structure of the solution-aged microalloyed graphene / aluminum composite material prepared in this embodiment. The multilayered graphene can be clearly observed. The measurement found that the thickness of the graphene in the composite material is about 8nm, and the spacing between the graphene layers is about 0.32nm. It can be seen that no needle-shaped or rod-shaped brittle phase Al4C3 is found at the interface, indicating that the interface reaction between the graphene and the aluminum matrix is suppressed.
[0142] 4. Mechanical properties test
[0143] The mechanical properties of the prepared graphene / aluminum composite material were evaluated by room temperature stretching. The model of the stretching machine is SS-8600 produced by Songshu Testing Instrument Co., Ltd. The oxide layer on the surface of the tensile specimen after heat treatment was removed with sandpaper, and the area of the cross section was measured with a vernier caliper. According to the proportional specimen, the corresponding gauge length was marked. The tensile specimen was cut from the block material by wire cutting, and the stretching direction was parallel to the force direction. During stretching, the stretching rate of the electronic universal testing machine was 2 mm / min.
[0144] In the graphene aluminum-based composite material prepared by the present invention, the strengthening of the matrix by alloy elements and the improvement of the graphene / aluminum interface are key factors for improving the mechanical properties of the composite material. Comparing the tensile mechanical properties of annealed pure aluminum, annealed 6061 aluminum, and the graphene / pure aluminum composite material prepared in Comparative Example 1 and the graphene / 6061 aluminum alloy composite material prepared in Comparative Example 2, the annealed pure aluminum is pure aluminum annealed at 340°C for 1 hour, and the annealed 6061 aluminum alloy is 6061 aluminum alloy annealed at 340°C for 1 hour.
[0145] Figure 7 This is a comparison chart of the tensile strength and tensile strain rate of pure aluminum and graphene / pure aluminum composites, 6061 aluminum alloy and graphene / 6061 aluminum alloy composites. a is pure aluminum and graphene / pure aluminum composites, b is 6061 aluminum alloy and graphene / 6061 aluminum alloy composites. The horizontal axis is the tensile strain rate and the vertical axis is the tensile strength.
[0146] from Figure 7 It can be seen that the tensile strength of annealed pure aluminum and annealed 6061 aluminum is 72.98MPa and 167MPa. Due to the addition of graphene, the tensile strength of graphene / pure aluminum composite material and graphene / 6061 aluminum alloy composite material increased to 235.31MPa and 325MPa respectively. The addition of graphene has a significant effect on improving the tensile strength of the two matrices; however, Figure 7 It can be seen that compared with the matrix, the addition of graphene reduces the plasticity of graphene / pure aluminum composites and graphene / 6061 aluminum alloy composites to 6% and 5% respectively. Although the addition of graphene improves the tensile strength of the material, the overall performance of the material is greatly reduced.
[0147] The annealed and solution-aged samples of the microalloyed graphene / 6061 aluminum composite material prepared in this embodiment were stretched. Figure 8 The tensile strength and tensile strain rate comparison diagram of the annealed composite material sample and the solution-aged composite material sample prepared in Example 1; it can be seen that the tensile strength of the microalloyed graphene / aluminum composite material in the annealed state reaches 266.31MPa, and the elongation reaches 12%; the tensile strength of the composite material in the solution-aged state reaches 304.14MPa, and the elongation is 7.5%. Compared with the non-microalloyed graphene / 6061 aluminum, the microalloyed graphene / 6061 aluminum composite material prepared by this patent has an elongation at break from 5% to 7.5%, an increase of nearly 50%, while maintaining a strength of more than 300MPa, and the complex plasticity has been significantly improved.
[0148] The tensile fracture after solution and aging was observed using a scanning electron microscope. Fig. 9 The tensile fracture scanning photos of the annealed composite material sample prepared in Example 1, a is magnified 100 times, b is magnified 200 times, c is magnified 500 times, and d is magnified 1000 times; Fig.10 These are scanning photos of the tensile fracture of the solution-aged composite material sample prepared in Example 1, where a is magnified 1000 times, b is magnified 2000 times, c is magnified 5000 times, and d is magnified 10000 times.
[0149] Fig. 9 and Fig.10Both show the presence of many fine dimples, and both show the characteristics of ductile fracture. By comparison, it can be seen that the dimples in the fracture of the composite material in the annealed state are deeper than those in the solution-aged state. The yellow arrows point to the graphene flakes that are broken or pulled out of the matrix when the composite material is tensile fractured. The graphene marked by the arrows is mostly distributed at the bottom of the dimples in the fracture and is basically perpendicular to the cross section. The edges of the dimples in the fracture of the composite material are still pure graphene that is breaking, indicating that the bridging effect of graphene bears the load before the composite material breaks.
Claims
1. A method for preparing a high-toughness microalloyed graphene / aluminum composite material, characterized in that: Here are the steps: Step 1: Mix graphene, silicone oil and aluminum alloy powder and perform ball milling to obtain a mixed powder; place the obtained mixed powder under a certain pressure for pressure holding treatment, and then perform heat treatment in a vacuum atmosphere to obtain a preform; Step 2: heating and melting pure aluminum, aluminum-scandium alloy and aluminum-zirconium alloy to obtain a mixed liquid, placing the preform obtained in step 1 and the mixed liquid under a certain temperature and pressure for pressure infiltration treatment, and cooling to obtain a sintered composite material; Step 3: subjecting the sintered composite material obtained in step 2 to extrusion deformation treatment to obtain an extruded microalloyed graphene / aluminum composite material.
2. The method for preparing a high-toughness microalloyed graphene / aluminum composite material according to claim 1, characterized in that: The method further comprises the step of annealing the extruded microalloyed graphene / aluminum composite material obtained in the step of 3 at 330-350° C. for 0.8-1.2 hours to obtain an annealed microalloyed graphene / aluminum composite material.
3. The method for preparing a high-toughness microalloyed graphene / aluminum composite material according to claim 2, characterized in that: The method further comprises the step of subjecting the annealed microalloyed graphene / aluminum composite material obtained in the step of the fourth step to a solution treatment at 530-550° C. for 0.8-1.2 h, water-cooling quenching, and then subjecting the composite material to an aging treatment at 165-185° C. for 5.5-6.5 h, to obtain a solution-aged microalloyed graphene / aluminum composite material.
4. A method for preparing a high-toughness microalloyed graphene / aluminum composite material according to any one of claims 1 to 3, characterized in that: Step 1: The graphene is a graphene nanosheet produced by a mechanical exfoliation process; the aluminum alloy powder is a 6061 aluminum alloy powder, and the chemical composition of the 6061 aluminum alloy powder includes, by weight percentage: Mg: 0.8-1.2%, Si: 0.4-0.8%, Cu: 0.15-0.4%, Mn: 0.15%, Cr: 0.04-0.35%, Ti: 0.15%, Fe: 0.7%, and the rest is Al and unavoidable impurities; the mass ratio of the graphene, silicone oil and aluminum alloy powder is 0.5-0.8:2-4:95-97.
5. The method for preparing a high-toughness microalloyed graphene / aluminum composite material according to claim 4, characterized in that: The ball milling in step 1 uses zirconia balls as the ball milling medium, the ball-to-material ratio is 5:1, the ball milling speed is 200-300 r / min, and the ball milling time is 1.5-2.5 h; the ball milling process is carried out in the form of forward rotation for 8-12 min → pause for 18-22 min → flip over for 8-12 min → pause for 18-22 min.
6. The method for preparing a high-toughness microalloyed graphene / aluminum composite material according to claim 5, characterized in that: The pressure of the pressure-maintaining treatment in step 1 is 55-65 MPa for 5-15 minutes, and the temperature of the heat treatment in step 1 is 390-410° C. for 5.5-6.5 hours.
7. The method for preparing a high-toughness microalloyed graphene / aluminum composite material according to claim 6, characterized in that: In step 2, the amount of aluminum-scandium alloy added to the mixed liquid is controlled according to the mass percentage of scandium element in the final product of 0.2-0.3%, and the amount of aluminum-zirconium alloy added to the mixed solution is controlled according to the mass percentage of zirconium element in the final product of 0.4-0.5%; the mass ratio of the preform to the mixed liquid is 6:
4.
8. The method for preparing a high-toughness microalloyed graphene / aluminum composite material according to claim 7, characterized in that: The temperature of the pressure penetration treatment in step 2 is 840-860° C., the pressure is 9.5-10.5 MPa, and the pressure holding time is 6-10 min.
9. The method for preparing a high-toughness microalloyed graphene / aluminum composite material according to claim 8, characterized in that: The temperature of the extrusion treatment in step 3 is 440-460° C., the extrusion ratio is 10:1, and the extrusion speed is 0.2-0.4 mm / min.
10. A high-toughness microalloyed graphene / aluminum composite material prepared by the method for preparing a high-toughness microalloyed graphene / aluminum composite material according to any one of claims 1 to 9, characterized in that: The alloy contains the following weight percentages: Mg: 1.4-1.5%, Si: 0.9-1.0%, Cu: 0.2-0.3%, Cr: 0.08-0.1%, Fe: 0.1-0.3%, Zr: 0.4-0.5%, Sc: 0.1-0.3%, and the rest are Al and other inevitable impurity elements.
Citation Information
Patent Citations
Preparation method of graphene / silicon carbide / aluminum composite material
CN108796397A
Preparation method of high-strength SiC nanowire reinforced aluminum based composite material
CN111235496A
Method for preparing cluster type aluminum-based composite material from graphene reinforced aluminum-based composite material waste
CN111945029A
Preparation method for dual model-structure graphene-reinforced aluminum matrix composite
CN111996407A
Particle double-phase AlTiCrNiCu reinforced SiCp / Al composite material and preparation method thereof
CN114592139A